Specific detection of RNA mutation at single-base resolution by coupling the isothermal exponential amplification reaction (EXPAR) with chimeric DNA probe-aided precise RNA disconnection at the mutation site. Issue 48 (29th May 2019) - Chang, Fu; Sun, Yueying; Yang, Dandan; Yang, Wenjuan; Sun, Yuanyuan; Liu, Chenghui; Li, Zhengping
Abstract : A chimeric DNA-aided RNase H-EXPAR approach is designed for the accurate and specific detection of RNA mutation at single-base resolution. Abstract : A chimeric DNA probe-aided RNase H-EXPAR approach is developed for the accurate and specific detection of RNA mutation at single-base resolution through a new site-specific RNase H cleavage mechanism.